Konstytucjonalizacja swobody przerywania ciąży we Francji w 2024 r. .......... 127 - Firek, Wojciech; Krzemiński, Marcin (Współczesne zmiany konstytucji w wybranych państwach europejskich: Pomiędzy partykularyzmem prawnym a wspólnotą doświadczeń, 2025)
CONSTITUTIONALIZATION OF THE FREEDOM TO TERMINATE PREGNANCY IN FRANCE IN 2024The article analyzes the 2024 amendment to the French Constitution that enshrined the freedom to terminate pregnancy. It reconstructs the legislative and constitutional context of the reform, examining its placement in Article 34 and the implications for the French system of fundamental rights protection. Although the amendment does not create a new subjective right, it elevates an existing statutory freedom to constitutional level, limiting the legislature’s ability to introduce future restrictions. The study argues that the change reflects a preventive strengthening of reproductive rights in response to global backsliding, particularly the U.S. Supreme Court’s reversal of Roe v. Wade. The French case, thus, illustrates how contemporary constitutional systems operate within a comparative network, reacting to external crises despite the absence of internal conflict.